Learning the Yellow Book with the Arabic Meaning of Pegon as Preserving the Intellectual Work of Indonesian Ulemas - Suryani, Khotimah; Mahmutarom, Mahmutarom; Ekaningrum, Ifada Retno; Junaidi, Mahbub (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2022)
The era of disruption is spurring the digitalization process in various aspects of life and showing the beginning of the democratization of knowledge, which gives individuals the opportunity to be creative and use productive technology. In this era, the pegon script began to be unrecognized by the millennial generation in Indonesia. This research focused on “The existence and implications of learning the yellow book with the Arabic meaning of pegon as preserving the intellectual work of Indonesian ulama in the era of disruption.” A qualitative model with a historical approach was used in this research. The results of this research: (a) the emergence of the era of disruption had a major impact on changes in lifestyle, social patterns, business, and technological digitalization, as well as the world of education. This changing trend demanded effectiveness and efficiency in energy, time, and costs; (b) Implications of learning the yellow book in Islamic boarding schools with the meaning of Pegon Arabic in this era of disruption was very useful and can be used as a means of preserving the intellectual work of Indonesian ulama.